PEMODELAN PERUBAHAN GUNA LAHAN (KASUS KABUPATEN MAJALENGKA) - Lia Warlina (Tataloka, 2016)
Land use change can be predicted by spatial modeling. One of spatial method to predict land use change is CLUES (Conversion of Land Use Changes and its Effect at small regional extent). The objective of the research is to determine factors that influence land use change in Kabupaten Majalengka and to predict its land use in the future. Data applied in this research project was biogeophysic, socio economic and existing land use data of Kabupaten Majalengka. Eight land use classes applied were shrub, forest, pond, dry land agriculture, pasture, settlement, and plantation and rice field. Land use classes were dependent variables; and biogeophysical and socio economical data were independent variables.  Binary logistic regression was applied to determine influenced factors to land use change. Factors that influence of type of land use’s occurrence were different for each type of land use. The value of the factors was used as an input in land use modeling using CLUES.  Scenario that used were scenario with land use change rate same as previous change. The simulation was applied for 12 years with the baseline data in the year of 2009. The simulation result shows that the land use types of shrub, forest, and plantation are decrease. The area that increased are land use types of dry land agriculture, settlement and rice field; however land use types of pond and pasture are remain constant.